On moment inequalities and stochastic ordering for weighted reliability measures - Broderick O. Oluyede; Mekki Terbeche (International Journal of Mathematics and Mathematical Sciences)
We obtain stochastic inequalities, error bounds, and classification probability for a general class of distributions. We introduce the notion of variability ordering via the probability functional and comparisons made for the weighted and the original distributions. We present moment inequalities, comparisons, and applications.